The First Translations into English of The Book of My Life by Saint Teresa in the Seventeenth Century - Pérez Bernardo, María Luisa (Estudios de Traducción, 2024)
In this essay, we will analyze the English translations of The Book of my Life by Teresa of Jesus, studying the different versions during the 17th century. Thus, we will show how the translations had a relevant position in the religious sphere of its time, and served to promote the tridentine spirit in a moment of religious expansion throughout Europe. Moreover, the versions had a pivotal significance among the Carmelites of the newly founded monastery in Antwerp; they served to preserve the spirit of Teresa of Jesus and her charisma, at a moment in which the conventual life was being renovated.
Keywords: The Book of My Life; translations; Council of Trent; the Antwerp Carmel